Why should mental health have a place in the post-2015 global health agenda? - McGovern, Peter (Int J Ment Health Syst, 2014)
BACKGROUND: The tenure of the Millennium Development Goals formally expires in 2015 and will be replaced with a new development agenda. The MDGs did not include goals or targets for mental health. Despite gathering momentum during the last 15 years, mental health has not enjoyed the same pace of progress as the sectors explicitly mentioned within the MDGs. This article outlines the evidence indicating that mental health should be firmly positioned in post-2015 health policy and discusses strategies to advance the global mental health agenda. DISCUSSION: The interactions between mental health and other development goals are numerous and complex. Consequently, investment in mental health pays dividends on a wider level than simply psychiatric clinical outcomes. Mental health’s reciprocal relationship with poverty is consistent with the strong focus on economic development, rather than health in isolation, detailed in the post-2015 UN statements to date. A focus on the quality of mental health care provided in low and middle-income countries deserves priority in the new health agenda. This should include consideration of the accessibility of mental health care and the use of evidence based diagnosis and management in these settings. SUMMARY: Lack of investment in the mental health of populations is a key driver of poverty and inequality in low and middle-income countries. Renewed focus on mental health post-2015 is an opportunity to address the global burden of mental disorders and make a positive impact on the wider development agenda.